Educação musical com estudantes trabalhadoras da pedagogia noturno/UFSM: mobilizações em grupo no estágio supervisionado - Reinicke, Priscila Kuhn Scherdien (2019)
The dissertation is linked to the Education and Arts Line (LP4) of the Postgraduate Program in Education of the Federal University of Santa Maria (UFSM) and is part of the research group "FAPEM: training, action and research in music education". The research had the general objective of understanding how the working students were related to the musical and pedagogical-musical knowledge constructed in a formation group (GF) and how they articulated them in the teaching of the supervised internship (ES). The specific objectives were based on the understanding of the group formation of working students, as a device that enhances the activities of Higher Education in music education; to understand how the process of musical and pedagogical-musical formation, together with the ES, is a trigger for ways of thinking and performing music education activities in ES, and to analyze the work of musical education and its meanings in the formative context for teaching in ES. The methodology was based on research-training (JOSSO, 2010a, 2010b, 2010c). From the methodological choice, which focuses on the formative dimension in the research process, a group of students in ES of Pedagogy Nightly (UFSM) was constituted a training device in musical education (OLIVEIRA, 2011; FERRY, 2004). Eight meetings with the GF were developed, with the participation of the researcher and six students. As data production instruments, oral and written narratives were used (LIMA, GERALDI C., GERALDI J., 2015, CHIENÉ, 2010). There were moments for collective talks during the training, organization of writing from field journals, and after the completion of training, the organization of an oral narrative interview. Student traineeship reports were also considered. All the moments were recorded from video recordings with the use of a cellular device. As results the research highlights the sharing of different knowledge, knowledge and experiences in the GF, moments that enabled the students to understand music as an area of knowledge in the insertion of their practices in basic education. In this process, certain musical and pedagogicalmusical knowledge were internalized and began to compose different proposals and musical experiences mobilized in the teaching of the ES. It is understood from the narratives and teaching experiences of working students that teaching music was marked by the formative potentiality for the integral and human development of its students.